Drug Persuaded Growing Defects of Teeth - Jalal Bashir Bhatti, Sabeen Saeed Butt, Hafeez Ullah Khan, Muhammad Tayyab, Junaid Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
The purpose of this research was to determine the impact that regularly prescribed drugs have on dental tissues. Certain drugs can cause sensitivity in dental tissues if they are used by pregnant women for an extended period. This research focused on a small set of drugs, such as aspirin, estrogen, and lithium that have been shown to have adverse effects on human tissue throughout the developing stages of pregnancy. Only female rabbits participated in the study. The animals in the experiment were split into four groups, and each group had (n=7) subjects. Three of them were for the study of drug treatments and the fourth one was taken as a control. They were administered drugs in predetermined doses based on their weights up until they gave birth. These rabbits were bred specifically to be utilized in scientific studies. Variations in tooth size, mineral content, and composition of enamel (the hard, protective layer of dental tissue), and ultrastructural changes in enamel surfaces were among the variables examined by scanning electron microscopy (SEM). At the age of three months, researchers analyzed the teeth to look for signs of congenital abnormalities that may have begun in utero. Six hundred seventy-two samples were analyzed using volumetric methods prior to tooth extraction. After the teeth were removed, 336 samples were analyzed using a scanning electron microscope and energy-dispersive X-ray spectroscopy to determine the mineral composition and examine the surface structure of the enamel (SEM-EDX). The chemical analyses and volumetric measurements showed a huge range of variance among samples between the control and experimental groups. The incisors and the premolars were found to be teeth with aesthetic and functional flaws. It was observed that the incisors and molars were aesthetically and functionally compromised teeth. However, this research has the potential to link long-term drug usage with dental drugs. It may also help future researchers focus on the role of drug-related factors in disease development. In dentistry, it could be useful for cosmetic and practical purposes. The results of the study were supposed to reveal which drugs should be avoided or used with caution during pregnancy and provide new avenues for further study. Keywords: drug persuaded, growing defects, teeth